An Overview of Farm Power and Energy in Agriculture (International Journal of Innovative Research in Engineering & Management, 2021)
Tillage, plant safety, planting, threshing, and harvesting  machines, as well as other stationary jobs like irrigation,  threshers, sellers, cleaners, graders, and so on, all require farm  electricity. Agriculture's direct and indirect energy consumption  can be separated. Direct energy requirements include land  planning, planting, harvesting, irrigation, food production, post harvest processing, storage, and transportation of agricultural  outputs and inputs. Farm power is now used to assist in  agriculture at various stages and to do comfort farming with the  aid of various farm power. The author of this study examined  farm power and energy in agriculture, as well as how farm power  aids agriculture at various levels. The author also covered human,  mechanical, and animal power, as well as electrical, solar, and  renewable energy in this review study. Farm electricity will be  utilized in huge numbers in the future, which will benefit those  working in agriculture.
Keywords: Agriculture; Energy; Farm Power; Human; Productivity